On simplified interpretations of limiting factors and dynamics of for abundance for some commercial fishes in the Far Eastern waters - Vyacheslav P. Shuntov (Известия ТИНРО)
Modern views on dynamics of some mass fish species, as walleye pollock Theragra chalcogramma , pacific salmon Oncorhynchus spp., and japanese sardine Sardinops melanosticta are critically analyzed. Recent tendency to formal and simplified approaches in explaining the status of populations and the factors limiting their abundance is noted, both for biologists and fishery oceanographers. It is reasoned by shortage of expeditionary researches combined with passion for formal indices and ignoring the role of population and endogenous factors in forming of new generations.